UMPSA remains country’s No. 1 technical university - Mimi Rabita, Abd Wahit (UMPSA, 2025)
PEKAN, 9 October 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) remains the best technical university in the country, having held the No. 1 position among the Malaysian Technical University Network (MTUN) institutions for four consecutive years.